Solid Waste Disposal Management Practices in Ghana, A Case Study of Subin Metropolis - Owusu-Ansah, Prince; Woangbah, Saviour Kwame; Anim, Benjamin; Azabu, Francis (Environmental Management and Sustainable Development, 2021)
Solid waste management is a societal problem both in developed and developing countries and studies have shown that most developing nations are struggling to find a lasting solution to this bane. The study therefore, sought to assess the waste management practices in Ghana using Subin Metropolis as a case study and offer some solutions to the challenges faced by resident and city authorities in managing the problem. Subin Metropolis a suburb of Kumasi, is considered as one of the highly-dense suburbs in terms of its human population and social activities. In this study, a set of structured questionnaires was administered to households selected randomly. The total number of households selected was based on statistics of the 2010 population census of one hundred and seventy-four thousand and four (174,004) inhabitants. with an annual growth rate of 4.8%, was used in projecting the number of inhabitants in the suburb for 2020 being the year under consideration as 253192, was adopted using the Slovin’s equation resulting in a sample size of four hundred (400). Data collected were analysed using SPSS and the results presented. Findings of the research reveal that despite the provision of dustbin by Subin sub metro authority and waste management companies, 32.25% of the residents use inappropriate storage receptacles including plastic bags to store their refuse temporarily in the house. 8.75% of residents dispose of their waste through waste companies using dump truck, 76% of the waste generated are evacuated through paid labourer for onward transportation to the few waste storage and collecting points within the metropolis. If the wastes at the storage point are not evacuated on time can lead to serious health implications. Lack of access roads is a major hindrance to effective waste management in the community due to poor spatial planning. Inadequate information and education on waste management and alternative strategies on managing waste is also another limiting factor that contributed to the poor sanitary condition in the Metropolis. This paper recommends using a multifaceted approach in solving the waste management menace through awareness creation, community engagement, information sharing as well as sustainable waste management systems such as waste reduction and recycling of waste. The paper also recommends that the city authority create more access roads in the community to improve upon waste services delivery.